Smart Digital Content Marketing in Embracing Indonesian Millennial Consumers - Aditya Yudanegara; Denny Saputera; Rizqi Muttaqin (UIN Raden Mas Said Surakarta, 2023)
The purpose of this research was to explore the effectiveness of the Smart Content Digital Marketing (SCDM) formula tailored to Indonesian millennial consumers within the context of online B2C businesses. The study aimed to develop a strategy that aligns with the distinctive characteristics of the millennial demographic while enhancing online business competitiveness. The research employed a combination of literature review and observational methods to formulate the SCDM strategy. It encompassed five main strategies: optimized social media content, influencer collaboration, diverse promotional approaches, consumer feedback engagement, and scheduled interactions. The findings revealed that the SCDM formula significantly resonated with Indonesian millennial consumers, resulting in enhanced engagement and loyalty towards online B2C businesses. The strategy's impact was observed through increased interaction rates, improved customer retention, and greater conversion rates. The personalized and tech-savvy approach of the SCDM strategy proved effective in capturing the attention of millennial consumers. The study's contribution lies in its development of a comprehensive strategy tailored to the nuances of the Indonesian millennial market. By strategically optimizing social media content, leveraging influencer endorsements, offering diverse promotions, maintaining a feedback loop, and implementing scheduled interactions, online businesses can effectively target and engage millennial consumers, fostering long-term loyalty and competitive advantage. In conclusion, this research underscores the significance of employing the SCDM formula for online B2C businesses targeting Indonesian millennials. The strategy's alignment with millennial characteristics and its positive impact on consumer engagement highlight its potential to reshape digital marketing approaches in an increasingly competitive landscape.